New Religions as Reflaction of the Postsecular State of the Contemporary Ukrainian Society - Grabovska Irina; Talko Tetiana; Vlasova Tetiana (Research Aspects in Arts and Social Studies Vol. 7, 2023)
The enhancing tendencies of postsecularism and globalization under the conditions of the social rifts in today’s Ukraine are especially significant in their influence on the quasi-religious context in the transformations of the religious worships in the communities of the contemporary Ukraine. These very factors erode the modernity basis of the society, and Ukraine, being in the process of completing the modernity phase, occurs in the contradictory situation of its intention to complete the modernization process and the tendencies of the antiglobalistic isolationism. The neoprotestant teachings and practices are analyzed in this article with the assertion of their leading impact on the principles of liberalism and consumerism. Neo-Oriental and new synthetic/syncretic religions produce significant influence on spreading globalistic views in the Ukrainian society. The marginality characteristics of the latest religions prove the authors’ idea that the values proposed by them are a serious challenge to the stereotypes of the essentialistic dichotomies of the Ukrainian patriarchal culture and traditional churches. The sociocultural and political context of globalization and postmodernism includes religious transformations axiomatically, and the impact of both on the late capitalism stage has been becoming more and more evident all over the world. Spreading its influence in various contexts and under the conditions, which can seem strikingly different, the culture of globalization and postmodernist drifts makes this process extremely complicated in the countries which are still between modernity and postmodernity. The processes of the label change are in the focus of the analysis with the stress on the substitution of the rationalistic foundation by quasi-scientific ideas and teachings in the contemporary Ukraine. The findings demonstrate that the very incompleteness of the modernity processes has led to the expansion of the quasi-scientific and quasi-religious techniques in the social and cultural life of Ukraine. In this context, the erosion of the modernity values results in spreading neoreligious worships, which began vivid at the end of the last century. It proves that the globalistic tendencies promote syncretic and Neo-Oriental religions and cults. The neopagan techniques and practices support antiglobalization movements.